Implementation of the Values of the Third Principle of Pancasila through Deep Learning-Based Learning with Baamnoozle Media - Fadhilah Aini; Nurul Husna (PT. Civil Military Center, 2025)
This research aims to examine the implementation of the values of the third principle of Pancasila, namely the Unity of Indonesia, through deep learning-based instruction utilizing the interactive Baamboozle media. The background of this study lies in the importance of internalizing the value of unity in national life, particularly within Indonesia’s diverse society. However, the teaching of Pancasila values in schools is still often conducted conventionally, making it less engaging and less effective in instilling the character of unity among students. This study employed a descriptive qualitative method with stages including planning, implementation, observation, interviews, and documentation in extracurricular RAM classes. The results show that the integration of deep learning—which emphasizes mindful, meaningful, and joyful learning—with Baamboozle media can enhance students’ understanding, motivation, and active engagement in internalizing the value of unity. Baamboozle, as an interactive edugame platform, proved effective in creating a collaborative and enjoyable learning atmosphere, enabling students to more easily understand and apply the value of unity in daily life. This research recommends the utilization of innovative, technology-based learning models to strengthen character education and foster a spirit of unity among Indonesia’s younger generation.